The Gow-Gates Technique for Mandibular Block Anesthesia: A Discussion and a Mathematical Analysis - Kafalias, Michael C. (1987)
Reliable profound mandibular block anesthesia is questionable when depositing the anesthetic solution at the lingula. Complications can occur and the needle may impact a number of important anatomical structures by deep penetration. The Gow-Gates technique for mandibular anesthesia obviates these problems. In this paper the Gow-Gates technique is reinterpreted using a geometrical approach based on lines and planes and is proved mathematically. In so doing a simple yet concise method of reaching the injection site is presented with a definite relationship between the anatomical pathway of the needle and a formal geometrical and mathematical pattern.